Autonomic Modulation for Cardiovascular Disease - Hadaya, Joseph; Ardell, Jeffrey L. (Frontiers in Physiology, 2020)
Dysfunction of the autonomic nervous system has been implicated in the pathogenesis of cardiovascular disease, including congestive heart failure and cardiac arrhythmias. Despite advances in the medical and surgical management of these entities, progression of disease persists as does the risk for sudden cardiac death. With greater knowledge of the dynamic relationships between the nervous system and heart, neuromodulatory techniques such as cardiac sympathetic denervation and vagal nerve stimulation have emerged as possible therapeutic approaches for the management of these disorders. In this review, we present the structure and function of the cardiac nervous system and its remodeling in disease states, emphasizing the concept of increased sympathoexcitation and reduced parasympathetic tone. We review preclinical evidence for vagal nerve stimulation, and early results of clinical trials in the setting of congestive heart failure. Vagal nerve stimulation, and other neuromodulatory techniques, may improve the management of cardiovascular disorders, and warrant further study.